Gestão da permanência no ensino superior: mapeamento de estudos sobre evasão e ações de permanência - Ramos Junior, Juarez Moraes (Universidade do Vale do Rio dos Sinos, 2021)
Dropout is one of the biggest problems in Brazilian higher education, resulting in a great challenge for students, institutions, and society. The present work has the general objective of gathering, systematizing, and analyzing information from research on the phenomenon of dropout that can contribute to the management of permanence in higher education. The defined methodology was exploratory-descriptive, adopting the bibliographical research of articles published in Brazilian periodicals, from the last 10 years, in Portuguese and peer-reviewed. A total of 149 articles were mapped whose empirical field encompassed discussions on the topic of dropouts and experiences of permanence actions. The mapped articles presented multiple dropout factors linked to students, institution, and external aspects. The predominance of articles on public institutions, the few articles that address distance education and the existence of only eight articles with reports of experiences of actions to extend the permanence of students in higher education stand out. This study also presents, as a product, a set of subsidies that can contribute to the performance of educational managers. The effectiveness of public student financing and assistance programs, as well as affirmative action, was observed, contrasting with few inclusion policies for people with disabilities and new vulnerable groups, such as the LGBTQIA+ community. The importance of public investment in educational policies that maintain students in public and private higher education was also perceived.
Keywords: Ensino superior; Gestão da permanência; Evasão; Gestão educational; Higher education; Permanence management; Dropout; Educational management; ACCNPQ::Ciências Humanas::Educação